The Southasian sensibility a Himal reader - Dixit, Kanak Mani (Sage Publications India Pvt. Ltd., 2012)
A collection of some of the best articles published over the past 25 years in Himal Southasian, South Asia's first and foremost regional news and analysis magazine.